The World Health Assembly Resolutions on eHealth: eHealth in Support of Universal Health Coverage - Al-Shorbaji, N. (Methods of Information in Medicine, 2013)
The World Health Assembly (WHA) of the World Health Organization (WHO) and three of the six WHO Regional Committees adopted a number of resolutions on eHealth: the use of information and communication technology for health. These resolutions have given legitimacy to eHealth as an area of work for WHO and its member states. The implementation of these resolutions will contribute to the achievement of the Millennium Development Goals (MDGs) and the Universal Health Coverage. eHealth has been per -ceived as reducing the cost of healthcare, improving quality and equitable access to health services.
Keywords: eHealth; information and communication technology; World Health Organization; World Health Assembly; millennium development goals; universal health coverage